The Arms Trade in Russian-Chinese Relations: Identity, domestic politics, and geopolitical positioning - DONALDSON, Robert H. (Institutional Knowledge at Singapore Management University, 2003)
Why would a declining power help arm a neighboring and once-hostile rising power? Current international relations literature cannot explain relationships in which one powerful country contributes directly to its long-term relative decline in order to make smaller, short-term gains. This study focuses on one example, the Treaty on Good Neighborly Friendship and Cooperation between the Russian Federation and the People's Republic of China, signed in Moscow on July 16, 2001. Presenting evidence that this alliance embodies a relationship that is based primarily on sales of arms from Russia to China, the authors argue that this association cannot be explained by current theory. Three variables appear most important to understanding the arms sales element of this case: declining relative position discloses the structural factors behind Russia's actions; domestic policy explains its willingness to make what had appeared as rash sacrifices; and identity issues explain the core motivations and interests of each actor.